Automated interaction may reduce emotional reactivity in VR: a randomized study with healthy participants - Diemer, Julia Elisabeth; Sich, Magdalena; Lange, Bastian; Müller, Mathias; Koller, Marius; Schäfer, Philip; Meixner, Gerrit; Brunnauer, Alexander; Zwanzger, Peter (Frontiers in Virtual Reality, 2025)
IntroductionVirtual reality (VR) has been investigated as a psychotherapy tool for 3 decades, with the most recent developments introducing automated self-help programs without direct therapeutic assistance. In particular, several publications have presented therapist-free VR exposure therapy for anxiety disorders as a way of improving patient access to psychological therapy. However, it is unknown whether the removal of interaction with a real person during VR exposure changes the emotional experience. The aim of this study was to test the effect of automated interaction on presence and emotion in VR. Both are important processes in VR-supported exposure therapy, with stronger emotional arousal and greater presence considered necessary for successful therapy.MethodsThis is a monocentric, randomized study comparing automated (auto) interaction in VR with experimenter-led (live) interaction during emotionally relevant VR scenarios (spiders; public speaking). The presence or absence of a psychophysiological recording device (smartwatch) was included as a second between-subjects factor. N = 64 healthy participants gave ratings of subjective emotional arousal and presence in VR.ResultsIn the spider scenario, arousal, our primary outcome measure, was significantly reduced in the auto condition, with no effect of the factor smartwatch. This effect was not seen in the public speaking scenario. For presence, in both scenarios, an interaction (condition × smartwatch) was significant, with participants in the auto condition reporting greater presence if they wore a smartwatch.DiscussionWe found that the design features of our VR system critically influenced presence and emotional effects. In particular, the reduced emotional arousal in the spider scenes means that automated setups might not be as suited for exposure therapy as therapist-led VR scenarios. To our knowledge, a direct comparison between automated and natural communication during emotional exposure in VR has not been made. However, our data indicate the importance of such comparisons. Our study thus addresses an important gap in the current VR literature. Future research will need to establish whether similar effects can be found in the target populations of exposure therapy, that is, patients with anxiety disorders, and whether such emotional effects might impact therapeutic outcomes.